Homepreneurship and Economic Wellbeing of Households: A Perspective Study of Selected Igbo Female Entrepreneurs in Ebonyi State - Gilbert Ogechukwu NWORIE; Fidelia N. NWORIE (CECCAR Business Review)

(untitled)
Purpose: The study examined the extent to which homepreneurship enhances economic wellbeing of households in Ebonyi State. Methodology: A descriptive survey research design was used. The sample consisted of 285 female entrepreneurs selected from a population of 994. Primary data were collected using a structured questionnaire. Analysis of research question and presentation of demographic profile of the respondents were done using frequency and percentage, respectively. Ordinal regression analysis was conducted to test the hypothesis. Finding: It was found that homepreneurship significantly enhances economic wellbeing of households in Ebonyi State (β = 0.387545; p-value = 0.012).Implication: In conclusion, the growth of home-based businesses can lead to enhanced economic wellbeing for households, providing financial stability, improved quality of life, and a reduction in gender-based economic disparities. To enhance the skills and business acumen of Igbo female entrepreneurs, training programs on business management, digital literacy, and financial planning should be introduced through local community centers to ensure that women acquire the knowledge necessary to run sustainable and profitable businesses. Originality: Unlike previous studies that primarily focus on challenges, theoretical models, or technological tools in homepreneurship, this article uniquely contributes original empirical evidence on how homepreneurship directly enhances household economic wellbeing in Ebonyi State, an area largely overlooked in existing literature.